Socio-economic inequalities in the use of healthcare services of the Montevidean elderly individual - Balsa, Ana; Ferres, Daniel; Ross, Máximo; Triunfo, Patricia (Estudios Económicos de El Colegio de México, 2009)
This study uses data from the 1999-2000 SABE survey to analyze socioeconomic inequities in healthcare access, utilization, and quality, for a sample of elderly individuals from Montevideo, Uruguay. We find horizontal inequity favoring the rich in the quality of access to medical visits (lower time spent travelling to the office and waiting in the office), in the probability of medical visits in the past 4 and 12 months, and in the use of preventive services (mamographies, pap scans, and prostate exams). The instrumental variables analysis suggests that inequities are probably underestimated when endogeneity is not taken into consideration.